Factors Associated with Mental Health Outcomes and the Level of Work Engagement Among Health Care Workers Exposed to Coronavirus Disease 2019 in Tunisia. (1st June 2022) - Betbout, I.; Amemou, B.; Ben Haouala, A.; Touati, Y.; Benzarti, M.; Zaafrane, F.; Mhalla, A.; Gaha, L.
Abstract : Introduction: Heath workers especiallyin the emergency rooms and emergency medical services are exposed to sustained stress which had increased due to the Pandemic situation Objectives: To search for factors associated with mental disorders among health workers during the Covid 19 pandemic Methods: Data were collected through a questionnaire, with demographic variables anddifferentscales to evaluate the degree of symptoms of depression, anxiety, insomnia, distress, and the level of work engagement(PHQ-9, GAD-7, ISI, IES-R, UWES-9). Results: Of the 217 participants, 46% were physicians, 42% were nurses and 12% were emergency medical technicians. We also found a femalepredominance of 66%, 55% were single and a total of 155 participants of whom 71% were frontline health workers. In our study, 54.8% of the HCWs had symptoms of depression, 68.2% had symptoms of anxiety and insomnia and 71.4% had symptoms of distress. Binarylogisticregressionanalysisshowedthat being married was associated with depression, anxiety, and insomnia, and being a frontlineworkerappeared to be a risk factor for depression and insomnia. Psychiatric support was an independentrisk factor for all psychiatric symptoms.In addition, living in a rural area was associated with depression, and age 31 or older was associated with anxiety. In addition, having a history of psychiatric illness was a risk factor for insomnia. Being a nurse was identified as a risk factor for psychiatric distress. We also found a moderatelevel of professional commitment to be a protective factor. Conclusions: Protecting healthcare workers is a crucial part of the public health response to the COVID-19 outbreak. Disclosure: No significant relationships.